Fracture toughness of TiAl-Cr-Nb-Mo alloys produced via centrifugal casting - A. Brotzu (Frattura ed Integrità Strutturale, 2012)
Fracture toughness of a TiAl base intermetallic alloy has been investigated at room temperature. The Ti-48Al-2.5Cr-0.5Nb-2Mo (at. %) alloy produced via centrifugal casting exhibits fine nearly lamellar microstructures, consisting mainly of fine lamellar grains, together with a very small quantity of residual β phases along lamellar colony boundaries. In order to determine the alloy fracture toughness compact tension specimens were tested and the results were compared with those available in literature.